2016
DOI: 10.3390/ijms17081351
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-331-3p Suppresses Cervical Cancer Cell Proliferation and E6/E7 Expression by Targeting NRP2

Abstract: Aberrant expression of microRNAs (miRNAs) is involved in the development and progression of various types of cancers. In this study, we investigated the role of miR-331-3p in cell proliferation and the expression of keratinocyte differentiation markers of uterine cervical cancer cells. Moreover, we evaluated whether neuropilin 2 (NRP2) are putative target molecules that regulate the human papillomavirus (HPV) related oncoproteins E6 and E7. Cell proliferation in the human cervical cancer cell lines SKG-II, HCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…One of potential mechanisms is through cellular microRNAs such as miRNA129-5p and miRNA331-3p [19, 20]. Zhang et al .…”
Section: Resultsmentioning
confidence: 99%
“…One of potential mechanisms is through cellular microRNAs such as miRNA129-5p and miRNA331-3p [19, 20]. Zhang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Here, in our study, miR-331-3p was shown to be significantly down-regulated in EAC patients with recurrence compared with those without. It has been demonstrated that overexpression of miR-331-3p inhibited the proliferation and migration of various cancer cells, suggesting the role of miR-331-3p as a tumor suppressor 22 26 . Functional data provided evidence that miR-331-3p could downregulate the expression of human epidermal growth factor receptor 2 (HER2).…”
Section: Discussionmentioning
confidence: 99%
“…miR-331 was reported to be dysregulated in various cancers. For example, miR-331 was found to be significantly upregulated in pancreatic cancer and cervical cancer [24,25]. Additionally, miR-331 was reported to be downregulated in colorectal cancer and ovarian cancer [26,27].…”
Section: Discussionmentioning
confidence: 99%